Antibodies from the sera of HIV‐infected patients efficiently hydrolyze all human histones. Issue 8 (22nd January 2016) - Baranova, Svetlana V.; Buneva, Valentina N.; Nevinsky, Georgy A.
Abstract : Histones and their post‐translational modifications have key roles in chromatin remodeling and gene transcription. Besides intranuclear functions, histones act as damage‐associated molecular pattern molecules when they are released into the extracellular space. Administration of exogenous histones to animals leads to systemic inflammatory and toxic responses through activating Toll‐like receptors and inflammasome pathways. Here, using ELISA it was shown that sera of HIV‐infected patients and healthy donors contain autoantibodies against histones. Autoantibodies with enzymic activities (abzymes) are a distinctive feature of autoimmune diseases. It was interesting whether antibodies from sera of HIV‐infected patients can hydrolyze human histones. Electrophoretically and immunologically homogeneous IgGs were isolated from sera of HIV‐infected patients by chromatography on several affinity sorbents. We present first evidence showing that 100% of IgGs purified from the sera of 32 HIV‐infected patients efficiently hydrolyze from one to five human histones. Several rigid criteria have been applied to show that the histone‐hydrolyzing activity is an intrinsic property of IgGs of HIV‐infected patients. The relative efficiency of hydrolysis of histones (H1, H2a, H2b, H3, and H4) significantly varied for IgGs of different patients. IgGs from the sera of 40% of healthy donors also hydrolyze histones but with an average efficiency approximately 16‐fold lower than that of HIV‐infected patients. Similar to proteolytic abzymes from the sera of patients with several autoimmune diseases, histone‐hydrolyzing IgGs from HIV‐infected patients were inhibited by specific inhibitors of serine and of metal‐dependent proteases, but an unexpected significant inhibition of the activity by specific inhibitor of thiol‐like proteases was also observed. Because IgGs can efficiently hydrolyze histones, a negative role of abzymes in development of acquired immune deficiency syndrome cannot be excluded. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : It is known, that administration of exogenous histones to animals leads to systemic inflammatory and toxic responses through activating Toll‐like receptors and inflammasome pathways. We present first evidence showing that 100% of IgGs purified from the sera of 32 HIV‐infected patients efficiently hydrolyze from one to five human histones. Several rigid criteria have been applied to show that the histone‐hydrolyzing activity is an intrinsic property of IgGs of HIV‐infected patients. The relative efficiency of hydrolysis of histones (H1, H2a, H2b, H3, and H4) significantly varied for IgGs of different patients. IgGs from the era of 40% of healthy donors also hydrolyze histones but with an average efficiency approximately 16‐fold lower than that of HIV‐infected patients. Because IgGs can efficiently hydrolyze histones, a negative role of abzymes in development of acquired immune deficiency syndrome cannot be excluded. The relative activity of IgG1, IgG2, IgG3, and IgG20 in the cleavage of five different histones leading to a formation of their fragments. The reaction mixtures were incubated for 6 h at 37 °C with electrophoretically homogeneous 0.05 mg/ml IgGs (lane 1–4). Lane C corresponds to the histones incubated for 6 h without abs. The arrows (lane SP) indicate the positions of molecular mass markers.